KAJIAN PERKEMBANGAN DESTINASI PARIWISATA TERHADAP PERUBAHAN PENGGUNAAN LAHAN DAN SOSIAL EKONOMI MASYARAKAT DI DESA SAKTI NUSA PENIDA, BALI - I Komang Gede Santhyasa; Komang Ayu Sari Galih; Putu Ekamai Pradana (Pranatacara Bhumandala: Jurnal Riset Planologi, 2022)
This study aims to identify the development of tourism destinations in Sakti Village, Nusa Penida. This study focuses on identifying and analyzing land use changes due to tourism activities in Sakti Village and their implications for the socio-economic conditions of the local community. The research uses mixed methods with data collection techniques using field observations and interviews. Data analysis was carried out using overlapping land use map techniques. The research found; 1) The development of tourism in Sakti Village has grown quite rapidly in terms of the completeness of attractions, amenities, and accessibility of existing tourism supporters. For DTW Crystal Bay Beach and Teluk Penida are more developed than Gamat Bay, the existing amenities in Sakti Village are also sufficient to accommodate visiting tourists, and access to Sakti Village, especially the road to Gamat Bay, is not adequate/proper; 2) Changes in dominant land use have changed, namely agricultural and livestock type land into settlements and tourism covering an area of 25.12 Ha; 3) The impact of tourism on socio-economics found from the existence of tourism activities in Sakti Village is the number of people who switch professions to the tourism sector. This is evidenced by the average level of income obtained by the community has increased by 1.375%.